Aiming for sustainability in food consumption through the reverse use of customer data – Insights from Gen Z’s sustainable behaviors - Hannukainen, Emilla (2025)
Consumers’ growing interest in sustainability, the servitization of the retailing industry, and technological advancements have transformed the food retail industry. To support consumers’ own value creation processes in everyday life, food retailers have introduced mobile services that enable the reverse use of customer data. Sustainable value co-creation in technology-mediated food consumption has been studied only to a limited extent, and there is little research on it from the perspective of Generation Z.